Functional Characterization of Clostridium tyrobutyricum L319: A Promising Next-Generation Probiotic for Short-Chain Fatty Acid Production - Yang, Zhihan; Amal, Fatima Ezzahra; Yang, Lei; Liu, Yuxin; Zhu, Liying; Zhu, Zhengming; Jiang, Ling (Frontiers in Microbiology, 2022)
Probiotics contribute a lot to human health and the occurrence of diseases. Correspondingly, probiotics' safety evaluation and probiotic properties have received increasing attention in the food industry and disease treatment. Clostridium tyrobutyricum L319 is a SCFAs (short-chain fatty acids)-producing strain isolated from Grana Padano cheese with a blowing defect. Our previous study has shown its safety at the genomic level. This study focused more on the safety evaluation and probiotic properties in vitro. According to the results, this strain has no potential virulence factors or the possibility of antibiotic resistance genes propagating. It also fulfilled several criteria to be used as a probiotic, including significant hydrophobicity under an acidic condition (pH 5.0) and resistance to simulated gastric juice and intestinal juice. Additionally, this strain was found to be tolerant to the harsh conditions of the external environment, including resistance to low (20 ℃) and high (50 ℃) temperatures, high salts (3% NaCl), and low pH (pH 5.0). Finally, we found that this strain could ferment prebiotics such as chito-oligosaccharides to produce SCFAs. It exhibited excellent growth performance whether using chito-oligosaccharide as a sole carbon source or combining glucose as the mixed carbon source. Furthermore, chito-oligosaccharide and glucose (1:1) mixed carbon sources were the optimal strategy for SCFAs production. Our findings demonstrated that this strain might be considered a promising candidate for future use as a probiotic to promote health benefits.